Agent's Wyoming mission - Bokal, Jennifer D. (Bokal, Jennifer D. Wyoming nights., 2021)
"Has a jailed serial killer somehow struck again? Agent Luis Martinez enlists his former friend Sheriff Julia McCloud to investigate, even though this new partnership unsettles them both. Personally, Luis feels the need to protect his PTSD-afflicted partner. Most of all, he realizes the undeniable attraction growing between them threatens their case ... as much as the serial killer taunting and targeting them."--Back cover.